2022
DOI: 10.1128/jvi.00671-22
|View full text |Cite
|
Sign up to set email alerts
|

The SARS-CoV nsp12 Polymerase Active Site Is Tuned for Large-Genome Replication

Abstract: Replicating large genomes represents a challenge for RNA viruses because fast RNA synthesis is needed to escape innate immunity defenses, but faster polymerases are inherently low-fidelity enzymes. Nonetheless, the coronaviruses replicate their ≈30-kb genomes using the core polymerase structure and mechanism common to all positive-strand RNA viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…Recent work showed that a nsp8-nsp7 (nsp8L7) fusion protein can efficiently function as a nsp12 cofactor and allows the contributions of each nsp8 of a coronavirus core complex polymerase activity to be delineated [35]. We produced SARS-CoV-2 and PEDV nsp8L7 fusion proteins with six-residue linker regions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work showed that a nsp8-nsp7 (nsp8L7) fusion protein can efficiently function as a nsp12 cofactor and allows the contributions of each nsp8 of a coronavirus core complex polymerase activity to be delineated [35]. We produced SARS-CoV-2 and PEDV nsp8L7 fusion proteins with six-residue linker regions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the core component of the RTC is the RNA synthase nsp12 [ 65 , 66 ], which stimulates its enzymatic activity with the help of cofactors nsp7 and nsp8 and together with nsp7 and nsp8 forms a core RdRp complex [ 54 ]. RdRp is a type of RNA synthetase that uses viral RNA as a template and four nucleoside triphosphates (NTPs) as substrates to synthesize RNA [ 67 , 68 , 69 , 70 , 71 ]. Currently, there are more than 30 crystal structures of SARS-CoV-2 RNA synthase in various functional states in the RCSB protein database [ 72 ].…”
Section: Drugs Targeting Rna-dependent Rna Polymerase Rdrpmentioning
confidence: 99%
“…In order to copy equivalent levels of genetic information, and to rapidly produce full-length copies to avoid innate immune activation, the RTC must be considerably faster. Several studies have now shown the SARS-CoV RdRp (nsp12) and associated cofactors (nsp7 and nsp8) replicate approximately 3–5X faster than other viral polymerases ( Campagnola et al, 2022 ; Seifert et al, 2021 ; Shannon et al, 2020 ). However, replication-rate and fidelity are in direct competition, and faster polymerases are inevitably more error-prone ( Fitzsimmons et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The guanine base of AT-9010 has more stacking power than the uracil of sofosbuvir, and likely helps to compensate for this loss in stability through interaction with residues in motif F of the fingers domain. This region is notably more open and flexible (in particular residue Arg555) in the CoV polymerase compared with other viral RdRps ( Campagnola et al, 2022 ). The missing interaction with the ribose of STP is therefore likely more detrimental, as the smaller uracil base is likely not well enough stabilized for efficient incorporation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation